ARTISTIC INTERPRETATION OF RELIGIOUS AND MYTHOLOGICAL MOTIFS - Mukhtorova Umidakhon Tolib kizi (Bright Mind Publishing, 2025)
We know that the Greeks are one of the oldest peoples with extensive cultural ties. About three thousand years ago, the world's first examples of literature and art began to be created in ancient Greece. Human ideas such as heroism, love, and patriotism were created in the guise of high art, based on religious and mythological motifs, which are also characteristic of these classical literary examples.
Keywords: Mythological motifs, patriotism, religious motifs, heroism, cultural ties, poetic era, literary phenomenon, social oppression, patron force.